2014
DOI: 10.5152/jtgga.2014.13109
|View full text |Cite
|
Sign up to set email alerts
|

What is the importance of omental metastasis in patients with endometrial cancer?

Abstract: Objective: To identify surgico-pathologic factors, survival, and the factors determining survival in patients with omental metastasis from endometrial cancer. Material and Methods:Patients with endometrial cancer operated on between 1993-2012 in our hospital and who had omental metastases were included. Patients with either uterine sarcoma or synchronous tumors were excluded.Results: Omentectomy was performed in 811 patients with endometrial cancer, and omental metastasis was found in 48 (5.9%) patients.Tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In their prospective report of 134 patients with clinical stage-1 endometrioid adenocarcinoma of the endometrium, Fujiwara, et al [13] proposed the removal of at least 10 × 5 cm of omentum for adequate detection of metastasis or a complete omentectomy if gross metastasis was suspected [13]. Turan, et al [14] studied 811 endometrial cancer patients and found that total omentectomy vs. infracolic omentectomy significantly increased the odds of detecting microscopic metastasis (11.3% vs. 2.1%, P < 0.001) [14].…”
Section: Commentmentioning
confidence: 99%
“…In their prospective report of 134 patients with clinical stage-1 endometrioid adenocarcinoma of the endometrium, Fujiwara, et al [13] proposed the removal of at least 10 × 5 cm of omentum for adequate detection of metastasis or a complete omentectomy if gross metastasis was suspected [13]. Turan, et al [14] studied 811 endometrial cancer patients and found that total omentectomy vs. infracolic omentectomy significantly increased the odds of detecting microscopic metastasis (11.3% vs. 2.1%, P < 0.001) [14].…”
Section: Commentmentioning
confidence: 99%
“…Saygili et al strongly recommended histopathologic examination, whereas Fujiwara et al stated that this was not necessary and that inspection would be sufficient [12,16]. However, there is no randomized controlled study on this subject and it has not been proven that total omentectomy contributes to survival [6]. Turan et al found no difference in survival in relation to the presence of micrometastases and macrometastases [6].…”
Section: Discussionmentioning
confidence: 99%
“…In the surgical treatment of endometrial cancer, omentectomy has been the topic of ongoing discussion for several years [2]. Significance and benefits of omentectomy in the surgical staging of EC are not well understood [6]. Due to the relatively low incidence of non-endometrioid tumors, outcomes for patients with these histologic subtypes are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Omental metastases are observed in 2.4%–8.3% of patients with endometrial cancer, and it is associated with a poor prognosis. [ 5 ] All guidelines for the treatment of endometrial cancer recommend omentectomy for visible peritoneal dissemination or in cases when the histology is papillary serous, clear cell, or carcinosarcoma. [ 2 ] However, omentectomy is not routinely recommended when the histology is endometrioid adenocarcinoma in the absence of macroscopic intra-abdominal metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Omentectomy in the presence of metastases may not improve the outcome as shown by Turan et al , who concluded that although omental metastases were associated with a poor prognosis, the effect of omentectomy on survival was controversial. [ 5 ] Turan et al performed omentectomy in 811 women with endometrial cancer, and omental metastases were present in 48 patients (5.9%), of whom 26 women had endometrioid carcinoma. Omental metastases were macroscopic in 60% patients and microscopic in 40% of the patients.…”
Section: Discussionmentioning
confidence: 99%